2021
DOI: 10.1039/d1ce00039j
|View full text |Cite
|
Sign up to set email alerts
|

Solid state structure and properties of phenyl diketopyrrolopyrrole derivatives

Abstract: The solid state supramolecular interactions of diketopyrrolopyrrole derivatives (DPPs) and their correlation with thin film optical properties are of particular interest because of the applications of these materials in organic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 107 publications
0
20
0
1
Order By: Relevance
“…The effect of using phenyl rings instead of thiophene was also investigated for single molecules by studying their solid-state features. 44 In this case where stronger hydrogen bonds are present and the phenyl is twisted outside the conjugation plane, a face-to-edge packing was observed hindering the π-stacking and lower charge mobility. Zhang et al 45 reported that, increasing the number of thiopenes and bithiophene rings between DPP units increases the glass transition temperature but does not change appreciably the mechanical properties.…”
Section: Introductionmentioning
confidence: 87%
“…The effect of using phenyl rings instead of thiophene was also investigated for single molecules by studying their solid-state features. 44 In this case where stronger hydrogen bonds are present and the phenyl is twisted outside the conjugation plane, a face-to-edge packing was observed hindering the π-stacking and lower charge mobility. Zhang et al 45 reported that, increasing the number of thiopenes and bithiophene rings between DPP units increases the glass transition temperature but does not change appreciably the mechanical properties.…”
Section: Introductionmentioning
confidence: 87%
“…The decrease in dihedral angle upon moving from phenyl substituents (~30°) to 5-membered rings (~7°) leads to significant changes in the photophysical properties of the resultant N , N -dialkylDPPs, with an especially notable bathochromic shift in absorption [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The lower dihedral angle allows the substituent to have a greater contribution to the π-system of the DPP core in the ground state [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in dihedral angle upon moving from phenyl substituents (~30°) to 5-membered rings (~7°) leads to significant changes in the photophysical properties of the resultant N , N -dialkylDPPs, with an especially notable bathochromic shift in absorption [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The lower dihedral angle allows the substituent to have a greater contribution to the π-system of the DPP core in the ground state [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Our study corroborates these earlier observations, i.e., the replacement of 1,4-phenylene with a 2,5-thienylene as a linker directly attached to DPP core ( 5 vs. 13 , 15 ) leads to a 100 nm red-shift of both absorption and emission ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эту корреляцию между кристаллическими структурами и электронными взаимодействиями в производных DPP можно объяснить с помощью модели взаимодействия экситонов Каши. В настоящее время N-незамещенные DPP, образующие нековалентные полимеры (2D) или кристаллы типа "кирпичная кладка" (3D) [1,2,[8][9][10][11][12][13][14][15][16][17], а также жидкие кристаллы [18] интенсивно изучаются ведущими мировыми лабораториями.…”
unclassified